The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/jms.193
|View full text |Cite
|
Sign up to set email alerts
|

Probing protein stabilization by glycerol using electrospray mass spectrometry

Abstract: This study shows that electrospray ionization mass spectrometry (ESI-MS), combined with a heated turbo ion-spray interface, allows monitoring protein stabilization by glycerol in solution. Measurements obtained with the two proteins lysozyme and cytochrome c are presented. The observed mass-to-charge (m/z) distributions reveal the stabilizing effect of the additive on the protein conformations against temperature and acid-induced unfolding, as well as against denaturation by acetonitrile. The data obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
6
24
1
Order By: Relevance
“…The envelope of the unfolded protein at pH 2.2 is centered on the peak of 17+ ion. These results are in agreement with previous measurements by regular3 or turbo‐ionspray7 ESI‐MS. Previous studies on the pH dependence of cyt c and lysozyme ESI mass spectra, in the presence of varying concentrations of glycerol as stabilizing agent, indicated that the main effect of pH changes in the range 4–2 is mediated by conformational changes 7.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The envelope of the unfolded protein at pH 2.2 is centered on the peak of 17+ ion. These results are in agreement with previous measurements by regular3 or turbo‐ionspray7 ESI‐MS. Previous studies on the pH dependence of cyt c and lysozyme ESI mass spectra, in the presence of varying concentrations of glycerol as stabilizing agent, indicated that the main effect of pH changes in the range 4–2 is mediated by conformational changes 7.…”
Section: Resultssupporting
confidence: 93%
“…Cyt c undergoes a highly cooperative, acid‐induced unfolding transition between pH 3 and pH 2 5. The unfolded state at pH 2 has been characterized by several physico‐chemical methods, including circular dichroism (CD), fluorescence, small‐angle x‐ray scattering5, 6 and ESI‐MS 3, 7. These studies showed that the polypeptidic chain under these conditions loses most of its native tertiary and secondary structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong pH dependence of protein stability is an obstacle to investigating the role of the pH on the ionization mechanism itself, uncoupled from conformational effects. The use of stabilizing agents, for example glycerol, has helped distinguish these two possible contributions to spectral changes in pH-variable experiments [26]. The results confirmed the predominance of conformational effects.…”
Section: Maria šAmalikova · Irena Matečko · Norbert Müller · Rita Grasupporting
confidence: 65%
“…However, the harsh conditions during the ionization process in MS are often detrimental to the preservation of protein conformation and the survival of noncovalent complexes. Many studies have examined the influence of the ionization process and the operating settings of ESI, including the curtain gas [16,17], the pressure in the ion source [18 -20], the temperature [21][22][23][24][25][26], the cone voltage [3,27], the spray mode [28], and the solvent composition [29,30]. To preserve the native protein conformation, a significant amount of effort has also been made on modifications to the ESI source.…”
mentioning
confidence: 99%